Application of a discovery to targeted LC–MS proteomics approach to identify deregulated proteins associated with idiosyncratic liver toxicity in a rat model of LPS/diclofenac co-administration. (4th May 2015) - Ramm, S.; Morissey, B.; Hernandez, B.; Rooney, C.; Pennington, S.R.; Mally, A.
Abstract: Increasing experimental and clinical evidence suggest a contribution of non-drug related risk factors (e.g., underlying disease, bacterial/viral infection) to idiosyncratic drug reactions (IDR). Our previous work showed that co-treatment with bacterial endotoxin (LPS) and therapeutic doses of diclofenac (Dcl), an analgesic associated with drug idiosyncrasy in patients, induced severe hepatotoxicity in rats. Here, we used an integrated discovery to targeted LC–MS proteomics approach to identify mechanistically relevant liver and plasma proteins modulated by LPS/Dcl treatment, potentially applicable as early markers for IDRs. Based on pre-screening results and their role in liver toxicity, 47 liver and 15 plasma proteins were selected for targeted LC–MS analysis. LPS alone significantly changed the levels of 19 and 3 of these proteins, respectively. T-kininogen-1, previously suggested as a marker of drug-induced liver injury, was markedly elevated in plasma after repeated Dcl treatment in the absence of hepatotoxicity, possibly indicating clinically silent stress. Dcl both alone and in combination with LPS, caused up-regulation of the ATP synthase subunits (ATP5J, ATPA, and ATPB), suggesting that Dcl may sensitize cells against additional stress factors, such as LPS through generation of mitochondrial stress. Additionally, depletion of plasma fibrinogen was observed in the co-treatment group, consistent with an increased hepatic fibrin deposition and suspected contribution of the hemostatic system to IDRs. In contrast, several proteins previously suggested as liver biomarkers, such as clusterin, did not correlate with liver injury in this model. Taken together, these analyses revealed proteomic changes in a rat model of LPS/Dcl co-administration that could offer mechanistic insight and may serve as biomarkers or safety alert for a drug's potential to cause IDRs.